1990
DOI: 10.1093/jnci/82.11.941
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Precursors of Cancer. Retinol, Carotenoids, and Tocopherol and Risk of Prostate Cancer

Abstract: We investigated the associations of serum retinol, the carotenoids beta-carotene and lycopene, and tocopherol (vitamin E) with the risk of prostate cancer in a nested case-control study. For the study, serum obtained in 1974 from 25,802 persons in Washington County, MD, was used. Serum levels of the nutrients in 103 men who developed prostate cancer during the subsequent 13 years were compared with levels in 103 control subjects matched for age and race. Although no significant associations were observed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
106
2
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(126 citation statements)
references
References 0 publications
17
106
2
1
Order By: Relevance
“…Three have shown a negative association with the risk of prostate cancer 89,90,91 and one showed no link. 92 In one study, 89 a statistically non significant 6.2% lower median lycopene level was demonstrated in those who developed prostate cancer compared to age and race matched controls (RR ¼ 0.50 95%CI ¼ 0.20 -1.29) between high and low quartiles of plasma lycopene and another (based on 581 subjects) 90 a statistically significant RR of 0.56% (95%CI ¼ 0.34 -0.91) was demonstrated when comparing high quintile with low quintile of plasma lycopene.…”
Section: Lycopene and Prostate Cancermentioning
confidence: 96%
“…Three have shown a negative association with the risk of prostate cancer 89,90,91 and one showed no link. 92 In one study, 89 a statistically non significant 6.2% lower median lycopene level was demonstrated in those who developed prostate cancer compared to age and race matched controls (RR ¼ 0.50 95%CI ¼ 0.20 -1.29) between high and low quartiles of plasma lycopene and another (based on 581 subjects) 90 a statistically significant RR of 0.56% (95%CI ¼ 0.34 -0.91) was demonstrated when comparing high quintile with low quintile of plasma lycopene.…”
Section: Lycopene and Prostate Cancermentioning
confidence: 96%
“…The major dietary source of lycopene is tomatoes, with the lycopene in cooked tomatoes being more bioavailable than that in raw tomatoes. Several prospective cohort studies have found associations between high intake of lycopene and reduced incidence of prostate cancer, though not all studies have produced consistent results [144,145]. Some studies suffer from a lack of good correlation between lycopene intake assessed by questionnaire and actual serum levels, and other studies measured intakes among a population that consumed very few tomato products.…”
Section: Reviewmentioning
confidence: 99%
“…More recently, we prospectively assessed the intake of >25 tomato-related food items in almost 30,000 men in the Prostate, Lung, Colorectal, and Ovarian (PLCO) cohort (17), and found no overall association of dietary intake of tomatoes and lycopene with prostate cancer [1,338 cases, odds ratio (OR), 5th vs. 1st quintile of lycopene intake 0.95; 95% confidence intervals (95% CI), 0.79-1.13], although inverse associations were suggested for some processed tomato products commonly cooked with fat (17). Because the bioavailability of tomato-derived lycopene, an extremely lipophilic antioxidant (18), varies profoundly with heat and fat application (19)(20)(21), some studies (22)(23)(24)(25)(26)(27)(28)(29) have relied on blood concentrations as an integrated measure of lycopene intake and absorption. Overall, results from these blood-based studies are inconclusive; some of the larger studies suggest the preventive effects of lycopene in subgroups with aggressive disease (16,17,22,28), older men (29), or men without a family history of prostate cancer (29).…”
Section: Introductionmentioning
confidence: 99%